Efficiency of OPU-IVEP-ET of fresh and vitrified embryos in buffaloes - Saliba, Wilson; Gimenes, Lindsay [UNESP]; Drumond, Roberti; Bayão, Henrique; Alvim, Múcio; Baruselli, Pietro; Bastianetto, Eduardo; Leite, Rômulo; Gasparrini, Bianca (My University, 2013)
The present study aims to report ovum pickup (OPU), in vitro embryo production (IVEP) and embryo transfer (ET) outcomes of fresh and vitrified buffalo embryos. For this purpose, 36 buffalo donors were submitted to 11 OPU sessions (n = 201). A total of 998 oocytes (5.0 ± 0.5/ donor/ session) and 584 viable oocytes (2.9 ± 0.3/ donor/ session) were recovered. Viable oocytes (grades 1, 2 and 3) were subjected to IVM, IVF (D0) and IVC. On D2, 54.5% of cleavage rate was obtained. Embryo yield on D7 was 44.9% (grade 1: 229 embryos, grade 2: 5 embryos and grade 3: 28 embryos). From this total, 115 fresh (grades 1 to 3) and 70 vitrified embryos (only grade 1) were transferred into recipients previously synchronized with fixed time embryo transfer (FTET) protocol. Vitrification was performed using the cryotop method. Pregnancy diagnosis in fresh and in vitrified groups were, respectively: 43.5% (50/115) and 37.1% (26/70) on 30 days after embryo transfer, and 41.7% (48/115) and 31.4% (22/70) on 60 days after embryo transfer. In conclusion, our results demonstrate the possibilities for commercial use of the techniques of OPU, IVEP and ET of fresh and vitrified embryos in buffaloes.
Keywords: Buffalo; Pregnancy; Vitrification